Does suppressing one's emotions increase the risk of all‐cause dementia among older adults?: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Lisko, Inna; Hall, Anette; Håkansson, Krister; Neuvonen, Elisa; Kulmala, Jenni; Ngandu, Tiia; Solomon, Alina; Kivipelto, Miia
Abstract: Background: An increasing body of evidence is showing that psychological risk factors are associated with Alzheimer's disease (AD) and other dementias. However, limited data exists on the effects of suppressing one's emotions on dementia/AD risk. The aim of the study is to explore if suppressing one's emotions is associated with a risk of all‐cause dementia in a population‐based sample of older adults. Method: The study uses data from a Finnish population‐based Cardiovascular Risk Factors, Aging and Dementia (CAIDE) study. In 1998, altogether 1137 individuals aged 65 to 79 years (mean 70.9 years) without dementia/AD responded to an inventory on ways of coping, where it was asked to describe how they usually respond to adverse events in life. For the statement "I suppressed my emotions from others", the response options ranged from 4 (fully agree) to 1 (fully disagree). Data on all‐cause dementia incidence were derived from clinical diagnoses during follow‐up in 2005–2008 and from a national register till the end of year 2009. Cox proportional hazards model was used in the analyses which were adjusted for age, gender, APOE ε4 allele, smoking, obesity and education. Result: Individuals who reported to fully agree on suppressing their emotions had nearly five times higher risk of developing dementia/AD as compared to those who fully disagreed on suppressing their emotions (Hazard ratio [HR] 4.93, 95% Confidence Interval [CI] 1.11–21.93). For those who fairly well agreed (HR 2.05, 95% CI 0.48–8.84) and quite strongly disagreed (HR 1.51, 95% CI 0.33–6.88) on suppressing their emotions the results were statistically non‐significant. Conclusion: When facing adverse events in life, suppressing one's emotions appears to be associated with an increased risk of developing dementia/AD. Further studies are needed to explore the mechanisms behind the found association.